An Ethical Modernity? : Hegel's Concept of Ethical Life Today - Chotaš, Jiří,; Matějčková, Tereza, (Critical Studies in German Idealism ;, 2020)
An Ethical Modernity? investigates the relation between Hegel's doctrine of ethical life ( Sittlichkeit ) and modernity as a historical category and a philosophical concept. In this collection of essays, the authors analyze Hegel's theory of ethical life from various perspectives: social ontology, social practices and beliefs, theory of judgment, relations between Hegel's theory of ethical life and Kant's ethics, Hegel's philosophy of family, relation of the modern market to 'European values', the ethos of state and of international relations, and Hegel's metaphilosophical commitment to philosophy. This volume is of importance to anyone interested in how Hegel's practical philosophy relates to us and our times.